Classroom Environment - Fraser, Barry J. (Routledge Library Editions: Education, 1986)
The increasing impact of performance based judgments on schools and teachers in the classroom has its critics and supporters. Some oppose the trend and seek to deny the importance of quantitative measures. Others have sought to find ways of implementing educational measurement constructively and with understanding of the concerns. Classrooms are where the operational business of learning takes place and it is on the quality of life within the classroom that the broader process of learning, concerns for the wider community and others, is nurtured. The climate of the classroom has a large impact on the final outcome measure to which so much interest is directed. To help our understanding of the dynamics involved much work has been done in the development and refinement of quantitative studies to this area by studying essential information about how teachers and students perceive the environments in which the work. Research on classroom climates has reached a practical and theoretical maturity and this volume offers an account of the developments that have taken place and the potential for understanding the classroom as a vital component of the curriculum. This book will also be an essential resource tool for anyone engaged in classroom research.